THE ROLE OF THE PRINCIPAL AS A MANAGER IN STRENGTHENING SCHOOL-BASED DATA PLANNING - Sudadi; Rasiman; Soedjono (SOSIOEDUKASI, 2025)
This study aims to describe the role of the school principal as a manager in the implementation of School-Based Data Planning at SD Negeri 2 Pamotan, Rembang Regency. Using a qualitative descriptive approach, the study involved in-depth interviews, direct observation, and documentation to collect data from the principal, teachers, and relevant school documents. The findings reveal that the principal plays a central role in all managerial functions—planning, organizing, implementing, and monitoring—related to PBD. The principal leads the IRB cycle (Identify, Reflect, Improve) by utilizing the Education Report data as a foundation for policy-making and school program development. Despite limitations in human resources and data literacy, the principal has fostered collaboration and reflective practices among teachers to enhance educational quality. The study highlights the importance of data-driven leadership in realizing effective school planning. The implementation of PBD has positively impacted literacy and instructional quality, demonstrating that strong principal leadership is key to achieving sustainable improvements in education